Chitosan and its antimicrobial potential – a critical literature survey - Raafat, Dina (Blackwell Publishing Ltd, 2009)
Chitosan, an aminopolysaccharide biopolymer, has a unique chemical structure as a linear polycation with a high charge density, reactive hydroxyl and amino groups as well as extensive hydrogen bonding. It displays excellent biocompatibility, physical stability and processability. The term ‘chitosan’ describes a heterogenous group of polymers combining a group of physicochemical and biological characteristics, which allow for a wide scope of applications that are both fascinating and as yet uncharted. The increased awareness of the potentials and industrial value of this biopolymer lead to its utilization in many applications of technical interest, and increasingly in the biomedical arena. Although not primarily used as an antimicrobial agent, its utility as an ingredient in both food and pharmaceutical formulations lately gained more interest, when a scientific understanding of at least some of the pharmacological activities of this versatile carbohydrate began to evolve. However, understanding the various factors that affect its antimicrobial activity has become a key issue for a better usage and a more efficient optimization of chitosan formulations. Moreover, the use of chitosan in antimicrobial systems should be based on sufficient knowledge of the complex mechanisms of its antimicrobial mode of action, which in turn would help to arrive at an appreciation of its entire antimicrobial potential.